Contribution of flax-cellulose nanocrystals on the structural properties and performance of starch-based biocomposite films - Emília Csiszár; Annamária Nagy; Erika Fekete (eXPRESS Polymer Letters, 2023)
Thermoplastic starch (TPS)/cellulose nanocrystal (CNC) films with glycerol or sorbitol plasticizers at 30 and 40% concentrations were prepared by casting over the whole composition range. The nanocrystalline cellulose was extracted from bleached flax by sulphuric acid hydrolysis. The haziness, tensile strength, thermal stability, and the effect of storage on crystal structure were investigated. Water vapor sorption of the neat TPS and flax-CNC films and water vapor permeability of the composites were measured at various humidity differences. The results showed that the high aggregation tendency of flax-CNCs significantly increases the opacity of films regardless of the type and amount of plasticizer. The reinforcing effect of nanocrystals can only be exploited at small concentrations (0–5%). However, 3–4% flax-CNCs result in a 15–25% reduction in water vapor permeability. Retrogradation of the TPS also reduced without changing the thermal stability. The properties of composites and their compositional dependence differ significantly from those of the composites prepared previously with cotton-CNC. Thus, knowledge of the properties of CNCs is essential for explaining the properties of polymer/CNC composites and the compositional dependence of properties.